Sie sind auf Seite 1von 25

p = F

A

( F A)

1 = 1 / 2 1 = 10 5 = 1000

p = F A ( F ⊥ A ) 1 = 1 / 2 1 =

p = F

A

( F A)

1 = 1 / 2 1 = 10 5 = 1000

1
1

F = 0

p = F A ( F ⊥ A ) 1 = 1 / 2 1 =

p = F

A

( F A)

1 = 1 / 2 1 = 10 5 = 1000

1

F F ⊥
F
F

F = 0

p = F A ( F ⊥ A ) 1 = 1 / 2 1 =

F

1

A

1

=

F

2

A

2

F

2

F

1

=

A

2

A

1

F 2 F 1 h 2 h 1
F 2
F 1
h 2
h 1

F 1

A 1

= F 2

A 2

F 2

F

1

= A 2

A

1

F 2 F 1 h 2 h 1
F 2
F 1
h 2
h 1

F

1

A

1

=

F

2

A

2

F

2

F

1

=

A

2

A

1

F 2 F 1 h 2 h 1
F 2
F 1
h 2
h 1

p 0 F
p
0
F

p 0 F

p 0 F
p
0
F

h

p =

ρ · g · h

+

p 0

ρ 10 3 / 3 p 0 :

p 0 F h p = ρ · g · h + p 0 ρ 10

p 0 F
p
0
F

h

p =

ρ · g · h

+

p 0

ρ 10 3 / 3 p 0 :

h

p 0 p 0 ρgh
p
0 p 0
ρgh

p 0 F h p = ρ · g · h + p 0 ρ 10

p 0 F
p
0
F

h

p =

ρ · g · h

+

p 0

ρ 10 3 / 3 p 0 :

h

p 0 p 0 ρgh
p
0 p 0
ρgh

p 0 F h p = ρ · g · h + p 0 ρ 10

F 1 h 1 , p 1 − F 3 F 3 F G h
F
1
h 1 , p 1
F
3
F 3
F G
h 2 , p 2
F
2

F < F

F = F

F > F

ρ V

F = ρ gV

F 1 h 1 , p 1 − F 3 F 3 F G h 2

∆l 1 v 1 ∆l 2 v 2 A 2 ,p 2
∆l 1
v 1
∆l 2
v 2
A
2 ,p 2

A 1 ,p 1

A 1 · v 1 = A 2 · v 2

∆l 1 v 1 ∆l 2 v 2 A 2 ,p 2 A 1 ,p 1

 

R

v

1,0

0,30

4 · 10 4

5 · 10 4

  R v 1 , 0 0 , 30 4 · 10 − 4 5 ·

∆l 1 ∆l 2 v 1 v 2 A 2 ,p 2
∆l 1
∆l 2
v 1
v
2
A 2 ,p 2

A 1 ,p 1

p

1

+ 2 ρv 2 =

∆l 1 ∆l 2 v 1 v 2 A 2 ,p 2 A 1 ,p 1